2019
DOI: 10.1186/s12889-019-7342-8
|View full text |Cite
|
Sign up to set email alerts
|

Do poor people in the poorer states pay more for healthcare in India?

Abstract: Background Rising health spending is associated with high out-of-pocket expenditure (OOPE), catastrophic health spending (CHS), increasing poverty, and impoverishment. Though studies have examined poverty and impoverishment effect of health spending in India, there is limited research on the regional patterns of health spending by type of health centers. This paper tests the hypothesis that the poor people from the poorer states of India pay significantly more for hospitalization in public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 46 publications
3
36
1
Order By: Relevance
“…Their sample is population based and nationally representative [41]. Researchers have observed that the above rounds provide comprehensive information on morbidity patterns, health care, type of providers (public or private), out of pocket expenditure for hospitalization [41,42]. NSS has reported adequate respondentcooperation rates in its 60th and 71st rounds.…”
Section: Methodsmentioning
confidence: 99%
“…Their sample is population based and nationally representative [41]. Researchers have observed that the above rounds provide comprehensive information on morbidity patterns, health care, type of providers (public or private), out of pocket expenditure for hospitalization [41,42]. NSS has reported adequate respondentcooperation rates in its 60th and 71st rounds.…”
Section: Methodsmentioning
confidence: 99%
“…NFHS-4 did not include any information on the actual cost of delivery care at the public health centre. Hence in line with previous literature, we have used the OOP payment for delivery care in private health centres as the proxy for the actual cost of delivery care in public health centres [22,49].…”
Section: Oop Payment and Cost Of Service On Institutional Deliverymentioning
confidence: 99%
“…To examine the economic inequality in the utilization of delivery care services in public/private health centre, we used CC and CI. CC and CI are commonly used by researchers to measure health inequality [49][50]. CC plots the cumulative proportion of the population (ranked by wealth) against the cumulative proportions of the population utilizing delivery care services in public/private health centres.…”
Section: Concentration Index (Ci) and Concentration Curve (Cc)mentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of awareness about disease management, inequitable distribution of health care facilities in rural areas coupled with high cost of SMBG test strips, financial constraints have led to comparatively decreased utilization of SMBG in rural areas. 14,15 The specialized health-care centres which are located in urban areas, generally provide more comprehensive medical care with greater focus on patient satisfaction with their medical care and patient-provider relationship. 1,14,15 This is also reflected in the present study wherein a significantly lesser percentage of diabetics from rural areas practised SMBG when compared to the diabetics who were residents of urban areas (Table 2).…”
Section: Discussionmentioning
confidence: 99%